MgCl2-MXene based nanohybrid composite for efficient thermochemical heat storage application. (March 2023) - Rehman, Ata Ur; Zhao, Tianyu; Muhammad, Ihsan; Rasheed, Shehla; Shah, Rahim; Altaf, Adnan Raza; Zhang, Fumin; Yun, Sining
Abstract: Thermochemical heat storage is a practical approach for overcoming the challenge in solar energy applications. Herein, we synthesize a novel MgCl2 /MXene (Ti3 C2 Tx ) composite sorbent by impregnation method for low-temperature thermochemical heat storage application. Various techniques, including Thermogravimetric coupled with Differential Scanning Calorimetric (TG-DSC), X-Ray, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) were applied to characterize the mechanical and thermal properties of MgCl2 /MXene composites. The result showed that Ti3 C2 Tx possess a larger specific surface area and the hydrophilic groups allow maximum MgCl2 adsorption without structural distortion. The TG-DSC studies showed that the fourth DSC peak of MgCl2 (181.33 °C) is shifted in composites MX/Mg 15 % (159.63 °C) and MX/Mg 10 %, (141.67 °C) toward lower dehydration temperature. The cyclicability study demonstrated that in the 10 consecutive rehydration cycles, MgCl2 shows 45 % decrease in the enthalpy, while Mg/MX 10 % and Mg/MX 15 % composites record 4 % and 10 % decrease, respectively. Water uptake kinetics highlighted that at 85 % RH, the highest water sorption was recorded for Mg/MX 15 % where it absorbs 2.21 g/g mass. The energy storage density result reveals that the maximum loading rate of MgCl2 ·6H2 O reaches 97.6 wt% for Mg/MX 15 % showed the highest enthalpy 2227 J/g at 85 % RH. Therefore, all the results indicate that MXene-based salt composites play an important role in thermochemical heat storage application, leading to a potential candidate for long-term heat storage. Highlights: A novel magnesium chloride hexahydrate/2D carbide (MgCl2 /MXene) thermochemical heat storage material was prepared. The fourth DSC peak of MgCl2 is 181.33 °C, while for MX/Mg 15% and 10%, the dehydration peak is 159.63 °C and 141.67 °C. MgCl2 /MXene provides the highest heat of hydration/dehydration highest enthalpy 2227 J/g at 85% RH. Mg/MX 10% and Mg/MX 15% composites at 85% RH can absorb water up to 1.97 and 2.20 g/g, At 85% relative humidity, the Mg/MX 10% and Mg/MX 15% had the highest Ƞv values of 0.547 and 0.772 GJ/m 3, respectively.